PERANCANGAN SISTEM INFORMASI PERSEDIAAN STOCK PARFUM DENGAN MENGGUNAKAN BAHASA PEMOGRAMAN VISUAL BASIC.NET DAN DATABASE ACCESS PADA TOKO GOFHA PERFUME - Eko Amri Jaya (Jurnal Sains dan Teknologi: Jurnal Keilmuan dan Aplikasi Teknologi Industri, 2016)
Perfume is a fragrance in the form of processed chemicals, with a fragrance that can make people become interested or merepon around us quickly, with this perfume will make situation become more attractive. By this author makes a thesis about Information System Design Inventory Stock Parfum with mengguanakan programming language Visual Basic.Net and Access databases to store Gofha Perfum. Technological developments at the present time is very rapid, beginning with local access to be able to access information from the world though. But behind it alldata management using computers should be is arranged in such a way, especially in gofha store perfume. leaders should always check the data perfume every day, month. Perfumesothat data can be managed properly andregularly it. Stock Inventory Information System Design can be coordinated in a computerized Perfume. Key Words: Information, System, Design